Differentiating the Impact of Structural and Motivational Green HRM Practices on Employees’ Voluntary Green Behaviors: : Evidence from PT Unilever Indonesia - Hidayati, Sri; Marlina (Jurnal SEKURITAS (Saham, Ekonomi, Keuangan dan Investasi), 2026)
This study examines how Green HRM (GHRM) practices affect employees’ Voluntary Green Behaviors at PT Unilever Indonesia. Using a PLS-SEM analysis of 94 employees, it assessed five GHRM dimensions. Results show that Green Performance Management, Green Rewards, and Green Employee Involvement significantly promote green behaviors, while Green Recruitment and Training do not. This highlights that motivational mechanisms not just structural practices drive eco-friendly actions. Procedural steps like recruitment and training require supportive leadership, ethical evaluation, and recognition to be effective. The study enriches sustainable HRM literature and offers practical insights for integrating environmental values into HR systems to improve sustainability.